Structural, magnetic, dielectric and magnetodielectric properties of Bi1-xCaxFe1-xMnxO3 in the morphotropic phase boundary region - Manjunath, B.; Thakuria, P.; Joy, P. A. (Materials Research Express, 2017)
Structural, magnetic, dielectric and magnetodielectric properties of Ca and Mn co-substituted bismuth ferrite, Bi1-xCaxFe1-xMnxO3 (0 <= x <= 0.4) are reported. Structural studies by Rietveld refinement of XRD patterns revealed rhombohedral R3c structure for x <= 0.11 and orthorhombic Pbnm structure for x >= 0.2. For compositions in the range 0.11 < x < 0.2, mixed phase behaviour is observed showing a morphotropic phase boundary (MPB) region. Magnetisation at room temperature increases with increasing Ca and Mn content, showing weak ferromagnetism. Coercivity and remanence initially increase and then decrease with increasing x, showing a maximum for x = 0.175 in the MPB region. Dielectric constant also shows a maximum value in the mixed phase region. Magnetodielectric (MD) studies revealed positive MD for the R3c phase and a negative MD for the Pbnm phase, showing a maximum MD (similar to 1%) for x approximate to 0.1 and crossover at x approximate to 0.175. The studies show strong interplay between the structure and properties, suggesting tuneable bismuth ferrite based compositions for magnetoelectric applications.

Structural and magnetic properties of La2Ni1-xCoxMnO6 compounds - Pramanik, Debabrata; Mukherjee, S.; Dan, Shovan; Nandy, A.; Pradhan, S. K.; Dasgupta, Papri; Poddar, Asok; Mukherjee, Manabendra; Manjunath, B.; Joy, P. A. (Materials Research Bulletin, 2018)
Single phase monoclinic La2Ni1-xMnO6 (x = 0.2, 0.4, 0.8) compounds, henceforth, referred as LNCxMO (x = 0.2, 0.4, 0.8) have been prepared by Sol-gel technique. The structural study and redox titration suggest that the samples are both La and O deficient. The generated atomic models using Rietveld refined structural parameters show octahedral distortion In the double perovskite structure. X-ray photoelectron spectroscopy (XPS) study has been used to determine the predominant valence states of Ni, Mn and Co ions. LNCxMO (x = 0.2, 0.4) are found to be Heisenberg ferromagnets whereas LNC0.8MO is a phase segregated system. In LNC0.4MO and LNO0.8MO, at temperatures above T-c, chi(-1)(T) curve shows the characteristics of Griffiths phase. The study of ac susceptibility and Isothermal remanent magnetization (IRM) discard the possibility of any glassy state at low temperatures. The antiphase boundaries (APBs), antisite disorders (ASDs) and oxygen vacancies play important roles in this system.